POLYMORPHISM IN THE ANGIOTENSIN-CONVERTING ENZYME (ACE) GENE AND ACE ACTIVITY IN TYPE 2 DIABETIC PATIENTS - A Nikzamir (Acta Medica Iranica, 2008)
Diabetes mellitus is a multifactorial disease. It has recently been shown that an insertion (I)/deletion (D) polymorphism exists in the angiotensin-converting enzyme (ACE) gene that can affect the serum ACE level. There are three genotypes: DD, DI, and II, with the ACE level being highest in DD, intermediate in DI, and lowest in II. In the present investigation, 170 patients with type 2 diabetes mellitus (T2DM) and 144 control subjects were studied. The ACE I/D polymorphism was determined by polymerase chain reaction (PCR) utilizing specific primers. ACE activity was determined spectrophotometrically. Distribution of ACE gene (I/D) polymorphism and allele frequencies in patients with T2DM were significantly different from those in control (P < 0.001); D allele frequency was 51% in T2DM vs. 48% in controls. The level of ACE activity was significantly higher in the DD genotype (91.1 ± 23.18) than those in ID (60.6 ± 22.8) and in II genotypes (36.8 ± 6.9). There was a significant difference in genotype distribution between the two groups (P < 0.001). New normal ranges of serum ACE level were determined for each genotype. Moreover, we found test sensitivity to be 62.3%. Serum ACE activity was significantly associated with ACE (I/D) gene polymorphism.